Skin Testing to Identify Safe Drugs for Patients with Rocuronium-Induced Anaphylaxis - Manzo Suzuki; Hajime Kawase; Azusa Ogita; Hiroyasu Bito (Case Reports in Anesthesiology)
Among patients who develop anaphylaxis during anesthesia, anaphylaxis caused by a neuromuscular blocking agent has the highest incidence. In patients who developed IgE-mediated anaphylaxis, and cross-reactivity among NMBAs is a concern in subsequent anesthetic procedures. We present a patient who developed rocuronium-induced anaphylaxis in whom the skin prick test (SPT) and intradermal test (IDT) could identify a safe drug to use in the subsequent anesthetic procedure. A 32-year-old female developed anaphylactic shock at the induction of general anesthesia. She recovered by administration of hydrocortisone and epinephrine. Skin tests including the SPT followed by the IDT revealed rocuronium as the drug that caused anaphylaxis and vecuronium as a safe drug to use for the subsequent general anesthesia. She safely underwent surgery with general anesthesia using vecuronium one month after the skin testing. There are not many reports on the effectiveness of the SPT followed by IDT in identifying the causative drug as well as a safe drug to use in the subsequent anesthetic procedure following anaphylaxis during anesthesia. The usefulness of the SPT should be re-evaluated.